Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Supercooled liquid phases of luminescent zero dimensional metal halide hybrids - Kumar Das, Deep; Marayathungal, Jumana Hasin; Palakkolil, Athira; Sarma, Dhritismita; Khan, Akram Aadil; Kumar, M. Praveen; Kudlu, Ashwath; Choudhary, Mahendra; Hathwar, Venkatesha R.; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Journal of Physical Chemistry Letters, 2025)
Chemical design of metal halide hybrids (MHHs) with suppressed melting point (T-m) allows access to glassy phases from their liquid-melts. Thermal phase change (crystal-melt-glass) properties of glassy MHHs (with glass transition temperature T-g > room temperature) have been exploited for device applications. However, room temperature stable supercooled liquid (SCL) MHHs (with T-g < room temperature), originating from glass-SCL phase change, remain inaccessible. Here, a molecular design strategy is reported to access ambient stable, melt-processable, SCL multimetallic bromide hybrids (Mn2+,Cd2+; Mn2+,Zn2+; Benzyltributylammonium) with low T-g (15-16 degrees C), low T-m (90-100 degrees C), green luminescence, and high optical transparency. Structural, optical, thermal, and computational analyses highlight chemical design principles and support dopant (Mn2+) based luminescence. Rheological measurements confirm the SCL phase that shows thermal hysteresis and estimate relaxation time scales. This work provides a new material platform showcasing enhanced melt-processability for fabrication of moldable devices, unravelling chemical makeup-property correlation and expanding the material phase types of MHHs.

Bright dual-phase organic luminescence from zero-dimensional lead halide hybrids via sensitized thermally activated delayed fluorescence for multifunctional applications - Kumar Das, Deep; Sarma, Dhritismita; Kumar, M. Praveen; Khan, Akram Aadil; Madhusoodhananan, Mahesh; Kudlu, Ashwath; Ajithkumar, Thalasseril Govindankuttykaimal; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Chemistry of Materials, 2026)
Metal halide hybrids have long celebrated their halometallate moieties as the luminescent center, leaving organic cations behind. Although the thermally activated delayed fluorescence (TADF) strategy has enabled efficient solid-state organic emitters, the complex molecular design required for TADF emitters has limited their facile integration into metal halide hybrid architectures. Here, we demonstrate a versatile strategy wherein a nonemissive organic moiety (benzyltributylammonium) is incorporated into a zero-dimensional disphenoidal Pb-halide hybrid, [(C19H34N)2PbCl4], resulting in efficient TADF-based dual-phase organic emission sensitized by halometallate units in the solid state (crystalline; amorphous). These materials exhibit strong PLQY (similar to 85%) and tunable organic luminescence (blue emission in crystalline phase; cyan emission in amorphous phase) modulated by the packing extent of organic moiety. [PbX4]2- units act as absorptive centers that sensitize organic cations showing TADF-based strong emission. Ground and excited state density functional theory calculations reveal the unique origin of sensitized TADF organic luminescence. Rheological measurements characterize relaxation dynamics of glass <-> supercooled liquid transitions, establishing correlations between molecular packing, phase, and emission characteristics. This first demonstration of dual-phase, sensitized TADF-based organic luminescence in lead halide hybrids establishes a new design paradigm that bridges molecular and solid-state photophysics, opening avenues for multifunctional applications in LEDs, optical thermometry, and security technologies.